Optimal control of a planar robot manipulator based on the Linear Quadratic Inverse-Dynamics design - Mosconi, Denis; Siqueira, Adriano Almeida Gonçalves; Fonseca, Everthon Silva (Journal of Mechatronics Engineering, 2019)
To ensure the correct positioning of the end-effector of robot manipulators is one of the most important objectives of the robotic systems control. Lack of reliability in tracking the reference trajectory, as well as in the desired final positioning compromises the quality of the task to be performed, even causing accidents. The purpose of this work was to propose an optimal controller with an inner loop based on the dynamic model of the manipulator and a feedback loop based on the Linear Quadratic Regulator, in order to ensure that the end effector is in the right place, at the right time. The controller was compared to the conventional PID, presenting better performance, both in the transient response, eliminating overshoot, and steady-state, eliminating the stationary error.